Technical efficiency analysis of container terminals in India - K. Chandrasekhar Iyer; V.P.S. Nihar Nanyam (Asian Journal of Shipping and Logistics (AJSL), 2021)
Despite the number of studies on the efficiency of container ports, most studies are of developed nations, and very few are of developing nations, such as India. Indian container ports are very critical due to their location advantage and their ability to handle transhipment traffic. There is a need to understand their performance at the micro-level, specifically the terminal level rather than that of the whole port. This paper focuses on the analysis of the technical efficiency of 26 container terminals in India using a data envelopment analysis approach for the years 2015-2018 and interprets it with respect to location advantage, administrative control and private control of terminal operations. The research explores the Malmquist index which measures productivity changes over a period of time and deconstructs them into two components, namely efficiency change, referred to as catch-up, and frontier shift. This study enabled the ranking of these terminals in terms of their performances. The relative efficiency of container terminals on the west coast of India is found to be better than that of the east coast of India, and the efficiency of container terminals operating under major ports is on a declining path when compared with that of minor ports. The private participation has also not seen similar productivity changes across all container terminals. Among the seven high performing container terminals identified through the analysis provided, the terminal at Tuticorin emerged as the most consistent one in terms of relative efficiency and growth in total factor productivity. The dominant factor influencing the efficiency of a terminal is found to be the size of the terminal, offering the advantages of economies of scale.
Keywords: 650; Container terminals; Data envelopment analysis; Efficiency; Malmquist index; Ranking